Temporal features of sitting, standing and stepping changes in a cluster-randomised controlled trial of a workplace sitting-reduction intervention - Samantha K. Stephens; Elisabeth A. H. Winkler; Elizabeth G. Eakin; Bronwyn K. Clark; Neville Owen; Marj Moodie; Anthony D. La Montagne; David W. Dunstan; Genevieve N. Healy (International Journal of Behavioral Nutrition and Physical Activity, 2019)
Abstract Background There is now a body of evidence on the effectiveness of interventions to reduce workplace sitting time. However, there has been limited reporting of how such interventions may impact behaviour both during and outside of work. Sitting, standing and stepping changes following a workplace intervention were examined across five timeframes (work time on work days; non-work time on work days; work days; non-work days; overall (i.e. work and non-work time on all days)), and the relationships between changes during and outside of work was assessed. Methods The cluster-randomised controlled trial, ‘Stand Up Victoria’, delivered a multi-component workplace-delivered intervention that successfully reduced workplace and overall sitting time (relative to controls). Separately, over the five timeframes, changes in device (activPAL3)-assessed outcomes — sitting; prolonged sitting (≥30 min bouts); standing; and, stepping — were compared between intervention (n = 114) and controls (n = 84), along with the time-course of sitting changes during work hours, using mixed models. The potential relationships of changes during work with changes outside of work were examined using compositional data analysis. Results On workdays, intervention participants significantly (p < 0.05) improved their activity profile relative to controls, with reduced sitting (− 117 min/8-h workday, 95% CI: − 141, − 93) and prolonged sitting (− 77 min/8 h workday, 95% CI: − 101, − 52); increased standing (114 min/8 h workday, 95% CI: 92, 136) and maintenance of stepping (3 min/8 h workday, 95% CI: − 7, 11, p = 0.576). Effects were nearly identical for time at work; similar but slightly weaker for overall; and, small and non-significant outside of work on workdays and non-work days. Improvements occurred at all times, but not equally, during work hours (p < 0.001). Correlations between changes during and outside of work on workdays were very weak in both the intervention group (r = − 0.07) and controls (r = − 0.09). Conclusions Sitting time was reduced almost exclusively during work hours (via replacement with standing), with reductions evident during all working hours, to varying degrees. There was no evidence of compensation, with minimal change in activity outside of work, in response to changes in activity at work. Future interventions may benefit from exploring how best to elicit change throughout the whole day, and across work and non-work domains. Trial registration This trial was prospectively registered with the Australian New Zealand Clinical Trials register (ACTRN12611000742976) on 15 July 2011